DIGITAL LITERACY OF SOCIAL MEDIA USERS IN MEDAN CITY IN FACING HOAX - Yovita Sabarina Sitepu; Hendra Harahap; Februati Trimurni, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Hoax and digitalization have become a threat to global democracy. During this pandemic, WhatsApp in collaboration with the Ministry of Communication and Informatics (Kominfo) has been successfully taken down 1, 759 hoaxes spreading on social media. Thus hoax content is circulating from January 23 to October 18, 2020. This study examines the literacy capability of social media users in Medan City in facing misinformation (Hoax). The purpose of this study is to describe the knowledge of social media users in Medan City regarding hoaxes; describing the process of spreading hoaxes among social media users in Medan City, as well as to identify the types of hoaxes mostly received and spread by social media users. The quantitative descriptive method is used in this study The samples of this study amount to 250 respondents selected in the accidental method. The results obtained from the aforementioned respondents show that respondents agreed that hoax is ‘a deliberate fake news. They stated that they had not been forwarding ‘splashy news’ that they received and do fact-check. On the other hand, when asked about why the ‘splashy news’ was forwarded, the respondents reasoned that they received the news from someone they trusted. In addition, the respondents each stated that they thought the news was useful as they believed the news to be true. The types of hoaxes most frequently received include lucky draws, socio-politics, governance, and health.